Results of targeted lymphadenectomy in patients with breast cancer cT1-3N1M0 after neoadjuvant systemic therapy - Sh. Sh. Abdulloeva; A. D. Kaprin; A. D. Zikiryakhodzhaev; E. K. Saribekian; E. A. Rasskazova; I. M. Onofriychuk; Ju. I. Volkova; U. Khomidi; D. B. Kodzoeva; L. P. Kazaryan (Исследования и практика в медицине)
Purpose of the study. To evaluate the results of targeted lymphadenectomy (TLAE) in patients with breast cancer (BC) cT1–3N1M0 after neoadjuvant systemic therapy (NAST).Patients and methods. The study represents a prospective analysis of 83 patients diagnosed with breast cancer in stage T1–3N1M0 who were treated in the Department of Reconstructive and Plastic Surgery of the breast and skin at the P. Hertsen Moscow Oncology Research Institute (Moscow, Russian Federation). The patients were divided into two groups: in the main group 1 (n = 45), TLAE was performed using a metal tag (clip) after surgery; in the control group 2 (n = 38), classical lymphadenectomy (LAE) was performed. The following characteristics were evaluated: the size of the primary tumor and its localization, the degree of malignan  cy (G), the biological subtype of the tumor, the number of sentinel lymph nodes (SLN), the number of metastases in SLN, damage to other lymph nodes, the number of patients who moved from cN1 to cN0. According to these characteristics, the two groups were comparable and there were no statistically significant differences. The effectiveness of NAST was assessed by the frequency of complete pathomorphological regression of the lesion of the studied tissue. The frequency of identification of sentinel lymph nodes was assessed with urgent cytological and routine pathomorphological studies.Results. In group 1, a complete pathomorphological response in the mammary gland was 37.8 %, in group 2 – 31.6 %. A complete pathomorphological response in the affected lymph node (N0) after neoadjuvant polychemotherapy (NAST) was achieved in 51.1 % of patients in group 1 and 52.6 % in group 2. The frequency of identification of sentinel lymph nodes during biopsy in both groups was 100 %. The frequency of identification of the installed tag was 100 %. The frequency of coincidences of the clipped lymph node with the sentinel lymph node was 65 %. In one case, migration of the installed label was noted. The efficiency of using the navigation explorer was 93 %.Conclusion. The results obtained confirm the expediency, feasibility and high efficiency of de-escalation of surgical intervention in the form of TLAE. Our study also demonstrates the relative simplicity and accuracy of using a metal tag to achieve TLAE goals.